Production of a Lipopeptide Biosurfactant by a Novel Bacillus sp. and Its Applicability to Enhanced Oil Recovery. (24th September 2013) - Varadavenkatesan, Thivaharan; Murty, Vytla Ramachandra
Abstract : Biosurfactants are surface-active compounds derived from varied microbial sources including bacteria and fungi. They are secreted extracellularly and have a wide range of exciting properties for bioremediation purposes. They also have vast applications in the food and medicine industry. With an objective of isolating microorganisms for enhanced oil recovery (EOR) operations, the study involved screening of organisms from an oil-contaminated site. Morphological, biochemical, and 16S rRNA analysis of the most promising candidate revealed it to be Bacillus siamensis, which has been associated with biosurfactant production, for the first time. Initial fermentation studies using mineral salt medium supplemented with crude oil resulted in a maximum biosurfactant yield of 0.64 g/L and reduction of surface tension to 36.1 mN/m at 96 h. Characterization studies were done using thin layer chromatography and Fourier transform infrared spectroscopy. FTIR spectra indicated the presence of carbonyl groups, alkyl bonds, and C–H and N–H stretching vibrations, typical of peptides. The extracted biosurfactant was stable at extreme temperatures, pH, and salinity. Its applicability to EOR was further verified by conducting sand pack column studies that yielded up to 60% oil recovery.